Analysis and Realization of Robot Actuator Based on Bidirectional Drivability Matrix. Issue 1 (July 2017) - Kawai, Yusuke; Yokokura, Yuki; Ohishi, Kiyoshi; Boonwong, Pattawan
Abstract: This paper proposes a bidirectional drivability matrix for enhancing the load-side operability of geared-motor. The interactive anti-resonant frequency in back-forward drivability is determined by analyzing the bidirectional drivability matrix of a two-inertia system. Load-side operability is low because a two-inertia system depends on friction. In contrast, a high operability at the load-side can be achieved using load-side torque control based on motor-side acceleration control. Simulations and experiments confirm the effectiveness of the analysis based on a bidirectional drivability matrix.